The Banks Profitability and Economic Freedom Quality: Empirical Evidence from Arab Economies - Omar Ghazy Aziz; Julie Knutsen (Journal of Banking and Financial Economics)
This study empirically examines the impact of economic freedom quality and global financial crisis on the banking sector profitability in the Arab region. The analysis is performed by employing system GMM estimation in panel data comprising of 14 Arab countries over the period 1985–2016. The study constructed an economic freedom index based on the economic freedom indicators. The findings indicate that greater economic freedom has positively influenced the profitability of the Arab banking sector. The results also suggest that the more profitable banks are those that have lower operating expenses against asset and income, better capitalized, more diversified and concentrated at economies having growth in the GDP. Furthermore, the global financial crisis in 2008 negatively impacted the profits of Arab banks.